Administrative Collection of State Debt : A comparative study - Khazael, Mohammed; Merza, Waleed (Journal of Legal Sciences, 2022)
The state’s finances consist of a set of rights that have a material value. Since the debtor’s failure to pay is conceivable, it is reasonable to assume that the State is in constant need of funds to manage its various activities. The state, but what distinguishes it from others in this case is its ability to fulfill the will of the individual without the need to resort to the judiciary to collect the debt.